The relationship between parenting style and social development among toddlers in Yogyakarta - Desi Rofita; Djauhar Ismail; Mohammad Hakimi (Journal of Health Technology Assessment in Midwifery, 2021)
Background: The development of children at preschool age is mentioned as the "Golden Period." At this time, the development of creativity, social awareness, emotional, and intelligence goes swiftly, therefore the parenting provided by parents from an early age will affect the future child's developmentPurpose: the major aim of the study was to know the relationship between parenting style and social development among toddlers in YogyakartaMethods: The design of this research was observational analytic with a cross-sectional design. The subjects of this study were mothers who have children aged 4-6 years, the sample used was 50 respondents. Data were analyzed using the chi-square test. An instrument using VSMS (Vineland Social Maturity Scale).Results: The results of the statistical test revealed that authoritarian parenting risked the children's social development by 5.5 times compared to authoritarian parenting, while permissive parenting risked children's social development by 7,5 times compared to authoritarian parenting. There is a significant relationship between parenting and social development of children with the value of CI 95% = 1.298-41.420 (p = 0.02). While the mothers' age does not have a significant relationship with the children's social development (p-value = 0.07), as well as the mothers' employment status does not have a significant relationship with the child's social development (p-value = 0.13).Conclusion: This study shows that there is a significant relationship between parenting and the social development of children, however, there is no significant relationship between age and mothers' employment status on children's social development.  Authoritarian   parenting is the most effective parenting approach to children's social development compared to authoritarian and permissive parenting.